2014
DOI: 10.1002/2014ja020204
|View full text |Cite
|
Sign up to set email alerts
|

Whistler‐mode waves inside flux pileup region: Structured or unstructured?

Abstract: During reconnection, a flux pileup region (FPR) is formed behind a dipolarization front in an outflow jet. Inside the FPR, the magnetic field magnitude and Bz component increase and the whistler-mode waves are observed frequently. As the FPR convects toward the Earth during substorms, it is obstructed by the dipolar geomagnetic field to form a near-Earth FPR. Unlike the structureless emissions inside the tail FPR, we find that the whistler-mode waves inside the near-Earth FPR can exhibit a discrete structure s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 58 publications
1
101
0
Order By: Relevance
“…The B Z fluctuations could be related to MHD waves, which are often observed near DFs (e.g., Zhou et al, 2014). But as was reported by Zhou et al (2014), the amplitude of these waves ≤ 2 nT. In our event the amplitude of strong B Z pulses exceeds 5 nT.…”
Section: Data Descriptionsupporting
confidence: 65%
See 2 more Smart Citations
“…The B Z fluctuations could be related to MHD waves, which are often observed near DFs (e.g., Zhou et al, 2014). But as was reported by Zhou et al (2014), the amplitude of these waves ≤ 2 nT. In our event the amplitude of strong B Z pulses exceeds 5 nT.…”
Section: Data Descriptionsupporting
confidence: 65%
“…During the gradual growth of B Z , numerous pulses of positive B Z field were observed. The B Z fluctuations could be related to MHD waves, which are often observed near DFs (e.g., Zhou et al, 2014). But as was reported by Zhou et al (2014), the amplitude of these waves ≤ 2 nT.…”
Section: Data Descriptionmentioning
confidence: 73%
See 1 more Smart Citation
“…Figures 4f and 4g show the electron phase space densities (PSD) f e in the EDR at 07:43:30.304 UT. In previous studies, streaming instabilities [Divin et al, 2012] and the associated electron holes [Goldman et al, 2014] at separatrices and the perpendicular anisotropy of suprathermal electrons [e.g., Khotyaintsev et al, 2011;Fu et al, 2014] have been suggested as two possible mechanisms responsible for the generation of whistlers. For the low-energy electrons (E < 100 eV), the PSD at θ = 180°is slightly larger than that at θ = 0°and θ = 90°(see Figure 4f), while for the medium-energy electrons (E > 100 eV), the PSD tends to be dominant in the perpendicular direction (Figure 4g).…”
Section: Electron Distribution and Wave Generationmentioning
confidence: 99%
“…DFs play a significant role in the magnetospheric dynamics (Zhou et al, 2010;Fu et al, 2011Fu et al, , 2012cFu et al, , 2014Ge et al, 2012;Hwang et al, 2014;Wang et al, 2016). The energetic ion anisotropies in the near-Earth plasma sheet show no strong correlation with Auroral Electrojet (AE) index, indicating that its acceleration sources are localized (Luo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%